As entrelinhas do contrato: uma análise sociossubjetiva dos parâmetros de produção e de recepção do gênero - Queiroz, Monique Galdino (2014)
In recent years, reductions in the interest rates led to increase the purchasing power of the Brazilian people. The recent facilities ensure the funding and affordable fees of movable and immovable property for the low-income consumer. Along with real estate, one of the sectors that have growth was the automobile. The difficulty of traffic in big cities is an indication that the number of vehicles has increased considerably (over the years). Given this reality, one textual genre has gained increasing evidence: the vehicle contract funding. The objective of this study is to analyze the production parameters of the vehicle contract funding as a textual genre, determining its linguistic and discursive features and the possible difficulties of interpretation by the contractors. For this, our corpus consist of four copies of the genre that come from different lending institutions, and eight interviews whose participants have different levels of schooling. For this purpose, our corpus consists of four copies of the genre come from different lending institutions and eight interviews using participants of different levels of schooling. The linguistic-discursive analysis of contracts is supported on Socio-discursive Interactionism (SDI) theoretical and methodological perspective evidenced in the work of Bronckart (1999). In order to unravel the complex web of textual organization, the author conceives the textual pastry metaphor, according to which, the texts are arranged in overlapping layers: infrastructure, textualization mechanisms and enunciative mechanisms (cf. Bronckart, 1999 p. 119). It was observed that the contracts analyzed generally follow a structural pattern and the thematic content is organized into two main parts: the first one presents the information of funding process in a chart and the second one has the clauses governing the contract. Regarding the infrastructure, the texts present predominantly an interactive discourse, with the presence of descriptive, explanatory and injunctive discursive sequences. Among the textualization mechanisms , the nominal cohesion mechanisms make reference and resume information set forth in the first part of the text, using acronyms, and explain it on the clauses. Finally, regarding the enunciative mechanisms, was observed in the samples that the producer-agent places the responsibility of was announced on the contractor in two different ways: Appropriating (making use of) his voice, using verbs in the first person, and by his signature at the end of the text, that make his the responsibility for the fulfillment of the statement. It was also verified that the inclusion of social voices, such as clauses and laws decrees can complicate the interpretive access of the gender to the interlocutors, since they do not have always knowledge of the contents of these resolutions. It was also noted that the interpretation difficulties are related to the observable lexical-semantic (the vocabulary of the legal department) and the observable order of paralinguistic (formatting elements of the text) (cf. BRONCKART, 1999, p. 80). It was concluded that, even with olds and known complaints, the attempts to reformulate the language and formatting the contractual text, although provided by law, have achieved very limited success, as it would be seen as a violation of the general integrity by members of the legal discourse community.